Silent orbitocranial penetration by a pencil. - Dinakaran, S (1998)
OBJECTIVE: To emphasise the value of computed tomography even in the absence of symptoms in a case of penetrating injury of the upper eyelid. METHODS: Case report. RESULTS: Although clinically asymptomatic, penetration of upper eyelid was associated with intracranial penetration that left a track in the brain parenchyma. CONCLUSIONS: Computed tomography of orbit and brain is an important investigation, even in seemingly trivial eyelid injury, to reveal the full extent of the damage.